‘‘O risco que corre o pau corre o machado’’: repressão e resistência camponesa em Rondônia, de Corumbiara ao acampamento Tiago Campin dos Santos, um olhar crítico à atuação insuficiente e ineficaz do Poder Judiciário frente a esses conflitos - Paixão, Mariana Gullo (2024)
This master's dissertation aims to address the historical origins, focusing on the Amazon region, more specifically in the state of Rondônia, of the transformation of land into capital and power, appropriated by agrarian elites who hegemonically maintain political, social and economic power. While there is a huge class of impoverished landless peasants who organize themselves in the fight for land, to gain democratic access to it, for those who live and work on it. In this context, the League of Poor Peasants of Rondônia and Western Amazonia (LCP) is researched, from its origins, from the Corumbiara Massacre in 1995, to its current activities, in one of its Camps in Rondônia, the Tiago Campin dos Santos Camp, which was created in 2020 and has resisted to this day. The LCP presents itself as a revolutionary combative movement whose main banner is the Agrarian Revolution and the radical takeover of large estate lands, which will be addressed here, covering fundamental points such as imperialism, bureaucratic capitalism, New Type Revolution and New Democracy. In this sense, we intend to observe the modus operandi of the State in relation to agrarian conflicts and the process of criminalization that is generated from the persecution of these movements that oppose the domains of the country's latifundiary base. The presence of the State as a permanent barrier of violence and its mechanism of converging illegalities into legalities is highlighted. The research also aims to draw a parallel between the repression and resistance that occurred both at the Santa Elina farm, in Corumbiara/RO, and at the Tiago Campin dos Santos Camp, in Porto Velho/RO, and to highlight the role of the Judiciary in these demands, as well as to highlight the presence of the agrarian oligarchies in these exclusion processes. The aim is to demonstrate that the uprising and organization that emanates from the peasantry is an inherent condition for survival, bringing the assumptions of the Right of Resistance and legitimate retaliation when faced with a profound social crisis. Based on the materialist, historical and dialectical methodology, the aim is to answer the following legal problem: what are the mechanisms of repression of the State and the actions of the Judiciary in the face of social movements fighting for land within the conflicts studied here.